-3x+12=-3(2y+2)

Simple and best practice solution for -3x+12=-3(2y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+12=-3(2y+2) equation:


Simplifying
-3x + 12 = -3(2y + 2)

Reorder the terms:
12 + -3x = -3(2y + 2)

Reorder the terms:
12 + -3x = -3(2 + 2y)
12 + -3x = (2 * -3 + 2y * -3)
12 + -3x = (-6 + -6y)

Solving
12 + -3x = -6 + -6y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3x = -6 + -12 + -6y

Combine like terms: 12 + -12 = 0
0 + -3x = -6 + -12 + -6y
-3x = -6 + -12 + -6y

Combine like terms: -6 + -12 = -18
-3x = -18 + -6y

Divide each side by '-3'.
x = 6 + 2y

Simplifying
x = 6 + 2y

See similar equations:

| -14x-8=-7x-12 | | 7x+5(-2x+3)=-3 | | -2(5p-1)-5p=-40-8p | | -4(x-2)=x+-7 | | 10+-1z=0 | | 3(x-9)=5x-27 | | N+5=-3-9 | | 120-12=4-14 | | 6x+2=6(x+3) | | -3+-1z=0 | | 4x^3-6x-36=0 | | -5(4x-5)+4x=7x-7 | | X=11250+-1x | | 3*6x=54 | | 55=8(5-3m)+5(3-8m) | | 2x+5=-3-9x | | 3x-63=2x+2 | | 8b(3b^3-12b^2-6)=0 | | 6x+6=-6+4x+18 | | 4(x-6)-3(4x+4)=-4x | | 175=5x+3(-6x+15) | | 2(x+8)-8= | | X+2915+x=14165 | | 31-3x=13-19x | | y=2x^2+11x+12 | | -5(2n-2)+7n=-14-7n | | x^2-8x-1600=0 | | -112-7x=10x+21 | | 1/2+4=-9 | | -89=7x+37 | | 0=-5(y+3) | | 3a+3b+2ab-6a+ab= |

Equations solver categories